2004
DOI: 10.1016/j.mcn.2004.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Long-term NR2B expression in the cerebellum alters granule cell development and leads to NR2A down-regulation and motor deficits

Abstract: N-methyl-D-aspartate receptor (NMDAR) composition in granule cells changes characteristically during cerebellar development. To analyze the importance of NR2B replacement by NR2C and NR2A subunits until the end of the first month of age, we generated mice with lasting NR2B expression but deficiency for NR2C (NR2C-2B mice). Mutant phenotype was different from NR2C knock-out mice as loss of granule cells and morphological changes in NR2C/2B cerebellar architecture were already evident from the second postnatal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
25
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 51 publications
4
25
0
Order By: Relevance
“…Gene targeting studies indicated that expression of NR2A and NR2C is essential for glutamatergic transmission in mature mossy fiber-granule synapses and participates in the coordination of complex motor movements (7). Long-term NR2B expression during development by incorporating the NR2B gene into the NR2C locus also showed a profound deteriorating effect on the cerebellar architecture and impaired motor coordination (32). The subunit switch of NMDA receptors thus significantly contributes to glutamatergic transmission in the mossy fiber-granule cell synapses.…”
Section: Discussionmentioning
confidence: 99%
“…Gene targeting studies indicated that expression of NR2A and NR2C is essential for glutamatergic transmission in mature mossy fiber-granule synapses and participates in the coordination of complex motor movements (7). Long-term NR2B expression during development by incorporating the NR2B gene into the NR2C locus also showed a profound deteriorating effect on the cerebellar architecture and impaired motor coordination (32). The subunit switch of NMDA receptors thus significantly contributes to glutamatergic transmission in the mossy fiber-granule cell synapses.…”
Section: Discussionmentioning
confidence: 99%
“…We addressed the importance of NR2B subunit during the migratory processes of cerebellar granule cells by using NR2C‐2B mice, where NR2B is over‐expressed instead of the NR2C subunit (Schlett et al. 2004).…”
Section: Discussionmentioning
confidence: 99%
“…NR2C −/− (Sprengel et al. 1998) and NR2C‐2B (Schlett et al. 2004) mice were housed in the Animal Facility of the Biological Institute, Eötvös Loránd University at 22 ± 1°C with 12 h light/dark cycles with ad libitum access to food and water.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations